ENGLISH LITERATURE STUDY PROGRAM STUDENTS MINDSET OF GRAMMAR FOR SPEAKING PRACTICE - sukma, riska ananda; Oktriyani, Angelina; Bernando, Jezen; Habibie, Andi Risqun; Tuastia, Selidia; Rulyanti, Merry (Journal Albion : Journal of English Literature, Language, and Culture, 2024)
Speaking in English language learning has significant benefit for communication in this era. Moreover, this is a requirement for English Study Program students since they get Speaking courses for several times in the university academic year. They also need this skill to support their professionalism in future career. However, in the real practice, the students seem to face obstacles to reach this objective. Accordingly, this study describes the student's problems in Speaking English in depth understanding. The data are taken from interview with 5 students of the second semester in English literature Study Program of Dehasen University. The results show that the students have problems in conducting English communication, namely low Grammar mastery, and nervousness. From this finding, it is expected that the students do some efforts to overcome their problems.